A synoptic review of Gomphomastacinae (Orthoptera: Eumastacoidea) from the Qinghai-Tibet plateau with a description of new species - Qiu, Shaoting; Xu, Sheng-Quan; Huang, Huateng (Zootaxa, 2021)
With unique climate, topography, and vegetation, the Qinghai-Tibet plateau is a special biogeographic region with richness of endemic species. However, the taxonomy and distribution of many insect groups on this plateau are still poorly known. Here, we synthesized a species checklist of subfamily Gomphomastacinae (Orthoptera: Acridoidea: Eumastacidae) for this region, while describing a new species: Myrmeleomastax wideis Qiu, sp. nov.. Images of the new species and the distribution map of all the known species are provided. Type specimens for the new species are deposited in the Zoological and Botanical Museum, Shaanxi Normal University, Xi’an, China (SNNU).